1959
DOI: 10.1152/ajplegacy.1959.196.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DCA on development of renoprival hypertension

Abstract: The administration of DCA (desoxycorticosterone acetate) to nephrectomized dogs drinking 1% saline speeds the development of hypertension. Studies on nephrectomized rats given 0.9% saline intraperitoneally show that this is not due to increased sodium intake or overhydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, the mechanism of corticosteroid-induced hypertension is not yet clear. Although renal sodium retention and intravascular volume overload contribute to the attendant hypertension, especially early in the course of the disease, non-renal mechanisms, such as the increase in peripheral vascular resistance, appear to play an important role in its development and maintenance [23]. It has been shown that corticosteroids potentiate the vasoconstrictor actions of vasoactive agonists such as 5-HT, NE and angiotensin II [8,9,11,[24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of corticosteroid-induced hypertension is not yet clear. Although renal sodium retention and intravascular volume overload contribute to the attendant hypertension, especially early in the course of the disease, non-renal mechanisms, such as the increase in peripheral vascular resistance, appear to play an important role in its development and maintenance [23]. It has been shown that corticosteroids potentiate the vasoconstrictor actions of vasoactive agonists such as 5-HT, NE and angiotensin II [8,9,11,[24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Despite repeated demonstration of the effects of aldosterone in both in vitro and in vivo experimental settings [2,3], its physiologic significance as a regulator of vascular tone in health and disease remains to be established.…”
Section: Aldosterone and Vascular Tonementioning
confidence: 99%
“…The downstream effects of GR activation within the arterial wall, and their influence on cardiovascular risk factors (such as hypertension), are imperfectly understood [5]. Glucocorticoids are essential for maintenance of blood pressure in healthy individuals [1], whilst their ability to increase peripheral vascular resistance in animals devoid of renal mass indicates that a non-renal mechanism contributes to glucocorticoid-induced hypertension [30]. A considerable body of evidence suggests that this non-renal mechanism may involve direct glucocorticoid-mediated alteration of EC and VSMC function [1].…”
Section: Introductionmentioning
confidence: 99%